2022
DOI: 10.3390/biomedicines10102531
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinomas of the Lung and Neurotrophin System: A Review

Abstract: Neurotrophins (NTs) represent a group of growth factors with pleiotropic activities at the central nervous system level. The prototype of these molecules is represented by the nerve growth factor (NGF), but other factors with similar functions have been identified, including the brain derived-growth factor (BDNF), the neurotrophin 3 (NT-3), and NT 4/5. These growth factors act by binding specific low (P75) and high-affinity tyrosine kinase (TrkA, B, and C) receptors. More recently, these growth factors have sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Raising awareness about this biomarker is crucial to employing a therapeutic approach that is highly effective and well-tolerated in treating both common cancers like NSCLC, where extensive tumor genotyping has become clinical practice, and rare tumors, where NTRK rearrangements are pathognomonic (80). Compared to other histological types, especially adenocarcinoma, NTRK1 and NTRK2 are more frequently expressed in epidermoid carcinoma (81). In a cohort of 686 individuals with epidermoid carcinoma, NTRK1 showed high specificity (92.8%) but mediocre sensitivity (71.6%).…”
Section: Ntrk Gene Fusionmentioning
confidence: 99%
“…Raising awareness about this biomarker is crucial to employing a therapeutic approach that is highly effective and well-tolerated in treating both common cancers like NSCLC, where extensive tumor genotyping has become clinical practice, and rare tumors, where NTRK rearrangements are pathognomonic (80). Compared to other histological types, especially adenocarcinoma, NTRK1 and NTRK2 are more frequently expressed in epidermoid carcinoma (81). In a cohort of 686 individuals with epidermoid carcinoma, NTRK1 showed high specificity (92.8%) but mediocre sensitivity (71.6%).…”
Section: Ntrk Gene Fusionmentioning
confidence: 99%
“…Researchers have demonstrated that inhibiting NGF or its receptor (TrkA) significantly retards tumor development, reduces pain-related activity, and ameliorated bone damage in sarcoma. The NGF/TrkA axis has also been implicated in the metastasis of various tumors, including breast cancer [22], lung cancer [23], colon cancer [24], pancreatic cancer [25], and prostate cancer [20]. In recent years, medicinal chemists have made considerable advances in our understanding of TRK inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation, as stated before, is a complex biological response triggered by the body's immune system to protect against harmful stimuli, such as tissue damage and pathogens. In this scenario, NGF can regulate the innervation and neuronal activity of peripheral neurons, inducing the release of immuneactive cytokines, neuropeptides, and neurotransmitters [14,[187][188][189]. Furthermore, NGF can also directly influence innate and adaptive immune responses through its interaction with various cells involved in the immune response, including mast cells, lymphocytes, and macrophages [28,190].…”
mentioning
confidence: 99%